Критерії кваліфікації та структура категорії валентності - Костусяк, Наталія Миколаївна (Кафедра україністики Варшавського університету, 2014)
The article is devoted to the theoretical grounds of the interlevel status of categories of valence as integral linguistic values associated with several grammatical areas, defining peculiarities of their structure. Differential features and the peculiarities of grammeme splitting in the interlevel category of valence have been determined; its connection with the lexical, semantic, syntactical and morphological levels of a language has been emphasised. We have differentiated between non-derivative verbal valence and the valence of declined adjectives, numerals and derived (verbal and adjectival) nouns, which are of a derivative character.
Keywords: міжрівнева категорія; непохідна валентність; похідна валентність; грамема; транспозиція; вербалізація; присудок